Efficacy of Low‐Dose Fluconazole for Primary Prophylaxis of Invasive Candida Infections in Patients With Acute Leukemia: A Double‐Blind Randomized Clinical Trial - Roghayeh Savary‐Kouzehkonan; Kourosh Sadeghi; Soroush Rad; Neda Alijani; Zohreh Baseri; Mohammad Vaezi; Seyed Asadollah Mousavi; Bita Shahrami (Cancer Medicine)
ABSTRACT Background Invasive fungal infections (IFIs), particularly Candida infections, are a significant cause of morbidity and mortality in patients with acute leukemia. While fluconazole is widely used for prophylaxis, the optimal dosing regimen remains uncertain. This study aimed to evaluate the efficacy of low‐dose fluconazole for primary prophylaxis against invasive Candida infections in patients with acute leukemia receiving intensive chemotherapy. Methods A double‐blind, randomized clinical trial was conducted with patients diagnosed with acute leukemia. Patients were assigned to receive either low‐dose (150 mg/day) or standard high‐dose (400 mg/day) fluconazole for primary prophylaxis against invasive Candida infections during intensive chemotherapy. The primary outcomes were the efficacy of antifungal prophylaxis and the safety profile. Results A total of 120 patients (60 per group) were enrolled. The overall incidence of Candida infections was similar between the groups (p = 0.615). Candida colonization was higher in the low‐dose fluconazole group during the first week, particularly with non‐albicans Candida at oral and subaxillary sites (p < 0.001). However, by the third week, both groups showed a significant decline in colonization, with the reduction in the oral cavity being statistically significant (p = 0.03). Aspergillosis occurred in 38.3% of patients, with no significant difference between groups (p > 0.99). Adverse events were similar in both groups (p > 0.05). Conclusion Low‐dose fluconazole is an effective alternative to high‐dose regimens for preventing Candida infections in acute leukemia patients, with similar efficacy and safety. The rising threat of aspergillosis highlights the need for targeted prophylaxis. Further research is needed to refine strategies for high‐risk patients. Trial Registration Iranian Registry of Clinical Trials (IRCT) number: IRCT20140818018842N37